Why has the Philippines remained a poor country? Some perspectives from growth economics - Michael M. Alba (University of the Philippines, School of Economics (UPSE), 2007)
Why has the living standard of the Philippines relative to that of the U.S. not risen unlike its Asian neighbors? Using data on national income accounts and the workforce from the Penn World Table (version 6.1) and years of schooling from Barro and Lee (2000) as well as a simple neoclassical model and some empirical methods of analysis employed in growth economics, this paper submits three interconnected answers: The country has been stuck in a low-growth trajectory. It is headed for a low steady-state level of output per worker, which explains its slow rate of long-term growth. Most significantly, its total factor productivity, at 20.9 percent of that of the U.S., is horrendously low, which explains its low convergence point. Improving its TFP is thus the key to solving the country's low living standard.
Keywords: 330; Wirtschaftswachstum; Lebensstandard; Arbeitsproduktivität; Philippinen